Is seroprevalence of anti-IGM CMV among blood donors relevant in India? - Kumar Harsh; Gupta P; Kumar Satish; Sarkar R (Wolters Kluwer Medknow Publications, 2008)
Background: Infection with cytomegalovirus (CMV) is more common in developing nations and the people belonging to the lower socioeconomic section of the society. The immunosuppressed population for whom CMV-seronegative blood products are requested is increasing due to advances in medical care. Aim: To study the prevalence of CMV antibodies among the different sexes and age groups in healthy blood donors. Materials and Methods: A retrospective study was done on 5600 serum samples stored frozen in a repository for CMV antibodies using the ELISA technique. Results: Five thousand three hundred and fifty (95.5%) were male and 250 (4.5%) were female. Four cases (0.071%) out of 5600 samples were positive for anti-IgM CMV with 95% Confidence Interval (95% C.I) of 0.02 - 0.17. Conclusion: In a developing country like India, screening for IgM antibody on a routine basis may not be feasible, given the likely positive yield to be low and the cost being high. It is recommended that in a tertiary care hospital, blood units to be transfused to neonates, organ transplant recipients, those suffering from malignancies and other immunocompromised patients should be screened for anti-IgM CMV or preventive strategies like universal leucodepletion to be implemented to decrease the transmission of CMV in these groups of patients.